Profile of Basic Technical Skills of Volleyball U-16 Club Athletes Wijaya Kusuma Champion 1 Level Cilacap District In 2025 - Burhaein, Erick; Prakoso, Bayu Satrio (Jurnal Pendidikan Jasmani (JPJ), 2025)
This study aims to describe the profile of basic volleyball technical skills in U-16 athletes of Wijaya Kusuma Club who won 1st place at the Cilacap Regency level in 2025. The basic volleyball technical skills measured include serving, passing, setting, smash, and blocking, which are important elements in the game of volleyball. This research uses a quantitative descriptive method with a survey approach. Data collection techniques were carried out through direct observation and interviews with coaches and athletes, as well as testing basic technical skills in the form of practical tests. The results showed that overall, U-16 athletes of Wijaya Kusuma Club had a very good level of basic technical skills, with the highest scores in passing and serving skills. The conclusion of this study is that the Wijaya Kusuma club has athletes with good basic technical skills because what supports this success includes intensive training, high motivation, and competition experience that is often followed by athletes. The results of this study are expected to provide insight for coaches and club managers in developing more effective training programs to improve athletes' basic technical skills in the future.